2021
DOI: 10.1016/j.omtn.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Testicular orphan receptor 4 (TR4) promotes papillary thyroid cancer invasion via activating circ-FNLA/miR-149-5p/MMP9 signaling

Abstract: The incidence and mortality of papillary thyroid cancer (PTC) have steadily increased. Although conventional therapies are very effective toward differentiated PTC patients, very limited therapeutic options are applicable to those patients with distant metastases. Therefore, better understanding of the molecular biology of metastatic PTC helps identify novel targets and facilitates the development of new therapies. In this study, we first found that testicular orphan receptor 4 (TR4) was significantly increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Thyroid cancer (TC) is a prevalent endocrine malignancy worldwide, accounting for approximately 300,000 new cases in 2012 and 40,000 deaths [ 1 3 ]. TC is commonly classified into anaplastic TC, medullary TC, and differentiated TC [ 4 ]. Papillary TC (PTC) is an epithelial-derived differentiated TC that accounts for most TC cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer (TC) is a prevalent endocrine malignancy worldwide, accounting for approximately 300,000 new cases in 2012 and 40,000 deaths [ 1 3 ]. TC is commonly classified into anaplastic TC, medullary TC, and differentiated TC [ 4 ]. Papillary TC (PTC) is an epithelial-derived differentiated TC that accounts for most TC cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, miR-149-5p was downregulated in the ISO-induced mouse hearts. Previous research has shown that the dysregulation of miR-149-5p is closely associated with malignant tumor progression, metastasis, and chemoresistance in gastric cancer (31)(32)(33), papillary thyroid cancer (34), colorectal cancer (35)(36)(37), and breast cancer (38). Additionally, miR-149-5p is also involved in the pathogenesis of inflammationassociated diseases, such as the PM 2.5 -induced inflammatory response (39), rheumatoid arthritis (40), and chronic obstructive pulmonary disease (41).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of circ-FLNA with this miRNA releases MMP9 from the inhibitory effects of miR-149-5p. Thus, the TR4/circ-FLNA/miR-149-5p/MMP9 axis has been identified as an important player in the pathogenesis of papillary thyroid cancer [ 16 ].…”
Section: Cell Line Studiesmentioning
confidence: 99%